Existence and Uniqueness of Periodic Solutions for a Kind of Second-Order Neutral Functional Differential Equation with Delays - Na Wang (Advances in Mathematical Physics)
We consider a kind of second-order neutral functional differential equation. On the basis of Mawhin’s coincidence degree, the existence and uniqueness of periodic solutions are proved. It is indicated that the result is related to the deviating arguments. Moreover, we present two simulations to demonstrate the validity of analytical conclusion.